Front Cover: Standardization and validation of phytometabolites by UHPLC and high‐performance thin layer chromatography for rapid quality assessment of ancient ayurvedic medicine, Mahayograj Guggul. Issue 10 (22nd May 2022) - Balkrishna, Acharya; Tomer, Meenu; Joshi, Monali; Gujral, Seema; Kumar Mishra, Rajesh; Srivastava, Jyotish; Varshney, Anurag
Abstract : DOI: 10.1002/jssc.202100935 Cover picture depicts the schematics for the chemical standardization of Mahayograj Guggul (MYG), a polyherbal ayurvedic medicine used to treat joints related ailments. MYG has been formulated by using 31 herbo‐mineral ingredients, some of the main ingredients (like Commiphora mukul ) are shown in mortar and pestle of the image. Modern analytical platforms like UHPLC, HPTLC and GC‐MS/MS were employed to standardize the complex MYG formulation. Fingerprints generated from liquid and gas chromatographic techniques represents the identified marker compounds and quality consistency of MYG. In the background, molecular structures of identified phyto‐compounds have been depicted.